PENINGKATAN KETERAMPILAN SOSIAL PADA MATA KUIAH PSIKOLOGI SOSIAL MELALUI IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MAHASISWA BKI SEMESTER V UIN SUMATERA UTARA TAHUN AKADEMIK 2017/2018 - Nunzairina Nunzairina (Hijri, 2018)
Problems of research is social skills improvement through the implementation of Student model of learning Problem Based Learning on Student BKI semester V North Sumatra Islamic State University academic year 2017/2018 this research It aims to find out students ' social skills improvement through the implementation of a model of learning Problem Based Learning on Student BKI semester V North Sumatra Islamic State University academic year 2017/2018. The subject in this study are students BKI semester V North Sumatra Islamic State University academic year 2017/2018 as much as one class of 30 students. The research object of this class action is the improvement of social skills of students in Social Psychology courses by using the learning model Poblem Based Learning in BKI semester V Islamic State University of North Sumatra Indonesia Years Academic 2017/2018. This research is carried out in implementation activities include class action class (PTK) in the form of early reflection activities and conduct observation to identify problems that occur in the classroom, learning, planning, implementing, observation and reflection. Implementation of the research action class (PTK) done 2 cycles, each cycle is carried out by 2 times and on each end of the cycle performed observation to find out the results of an increase in Student social skills. Research results can be presented that the categories percentage of Student social skills cycle observations I meetings I categories include low i.e. of 46.67%, cycle I encounter II categories include high amounting to 33.33%, cycle cycle II meeting I categories include high i.e. of 53.33%, and cycle II II meetings including very high i.e. categories of 90.00%. Can thus be expressed conclusion that the implementation of the learning Problem Based Learning model can improve the social skills of students in Social Psychology courses in the academic year of V semester BKI 2017/2018.Keywords: Model Of Learning Problem Based Learning, Student Social Skills.